Job Stability, Earnings Dynamics, and Life-Cycle Savings - Moritz Kuhn; Gasper Ploj (Institute of Labor Economics (IZA), 2020)
Labor markets are characterized by large heterogeneity in job stability. Some workers hold lifetime jobs, whereas others cycle repeatedly in and out of employment. This paper explores the economic consequences of such heterogeneity. Using Survey of Consumer Finances (SCF) data, we document a systematic positive relationship between job stability and wealth accumulation. Per dollar of income, workers with more stable careers hold more wealth. We also develop a life-cycle consumption-saving model with heterogeneity in job stability that is jointly consistent with empirical labor market mobility, earnings, consumption, and wealth dynamics. Using the structural model, we explore the consequences of heterogeneity in job stability at the individual and macroeconomic level. At the individual level, we find that a bad start to the labor market leaves long-lasting scars. The income and consumption level for a worker who starts working life from an unstable job is, even 25 years later, 5 percent lower than that of a worker who starts with a stable job. For the macroeconomy, we find welfare gains of 1.6 percent of lifetime consumption for labor market entrants from a secular decline in U.S. labor market dynamism.
Keywords: J64; E21; E24; 330; employment risk; job stability; consumption-saving behavior